Perbandingan Penggunaan Bakteri Asam Laktat dan Ragi Instan pada Proses Fermentasi Roti - Nia Arrizqi Alviani; Intan Wahyuni; Miftahul Jannah; Tari Oktarisya (Ma'soem University, 2023)
Bread is a snack made from wheat flour and has a high consumption value in society. Bread can be made using sourdough or yeast as one of the main ingredients in its manufacture. Sourdough has advantages in terms of nutrition compared to the nutrients contained in yeast. However, it is not yet known how the differences in the use of sourdough and yeast in the process of making bread. For this reason, this study aims to compare and identify the differences in the use of sourdough and yeast in bread making. This study used an experimental method to compare the two materials. Based on the experimental results, it was found that in terms of bread dough development with yeast it was faster than sourdough and had a distinctive aroma and texture on each bread.